ENGAGING FUTURE SHIP ENGINEERS IN DISTANCE STEM EDUCATION (Journal of Information Technologies in Education (ITE), 2021)
The research summarizes the modern approaches to STEM education for future ship engineers: the problem-based learning activities, not standard or typical designs and problems, the integration of STEM subjects, the introduction of innovation to teaching methods in relation to each subject, the multidisciplinary approach to STEM education that implies the integrative environment for teaching STEM subjects. It is highlighted that in the era of industrialization, literacy and work skills were important, but in the post-industrial era, the technological aspects of youth development have come to the fore. It has been also determined that awakening a creative approach, interest in a comprehensive perception of the subject of study, critical thinking, STEAM teachers give students more than just knowledge – they also give them skills, a taste for knowledge and work, a desire to immerse themselves in self-development, to love the learning process itself. The study presents the content-related and structural characteristics of STEM targets, approximate educational outcomes, content, final assessment, focus areas (problem solving situation), technological curriculum design methods provided by STEM techniques. The research describes the hands-on experience of involving teachers in creating STEM projects for ship engineers in distance STEM education. It is concluded that it is impossible to overestimate the prospect of using information technology in the implementation of STEM programs. Another conclusion is that graduates of educational institutions that actively use information technology in medicine, construction, chemistry, physics, biotechnology and other fields of science are becoming more and more in demand.
Keywords: STEM education, ship engineers, MOODLE, creative task solving, information technology